Power relations, institutional violence, and the potential for social change: A study of D.P. Season 2 - Teza Ramananda Febriana; Rahmat Wisudawanto; Erwin Kartinawati (Societa: Journal of Society and Change, 2026)
Power relations and institutional violence are frequently represented symbolically in audiovisual media, yet studies linking such representations to their potential for social change remain limited. This study aims to analyze the representation of power relations in D.P. Season 2 and evaluate its strategic potential to promote social change. A qualitative approach was employed using Roland Barthes' semiotic analysis of five representative scenes, followed by a SWOT-based evaluation. The findings reveal that D.P. Season 2 represents power relations through structural violence, information manipulation, gender discrimination, and legal injustice legitimized by a hierarchical institutional culture. The SWOT evaluation indicates that these representations have considerable potential to foster public critical awareness, despite limitations in media representation and institutional resistance. This study contributes by integrating semiotic analysis with strategic evaluation to explain the relationship between media representation, power relations, and social change. Abstrak Relasi kekuasaan dan kekerasan institusional kerap direpresentasikan secara simbolik dalam media audiovisual. Namun, kajian yang menghubungkan representasi tersebut dengan potensi perubahan sosial masih terbatas. Penelitian ini bertujuan menganalisis representasi relasi kekuasaan dalam D.P. Season 2 serta mengevaluasi potensi strategisnya dalam mendorong perubahan sosial. Penelitian ini menggunakan pendekatan kualitatif dengan analisis semiotika Roland Barthes terhadap lima adegan representatif yang kemudian dievaluasi menggunakan kerangka SWOT. Hasil penelitian menunjukkan bahwa D.P. Season 2 merepresentasikan relasi kekuasaan melalui kekerasan struktural, manipulasi informasi, diskriminasi gender, dan ketidakadilan hukum yang dilegitimasi oleh budaya hierarkis institusi. Evaluasi SWOT memperlihatkan bahwa representasi tersebut memiliki kekuatan dalam membangun kesadaran kritis masyarakat, meskipun masih menghadapi keterbatasan representasi serta resistensi institusional. Penelitian ini berkontribusi dengan mengintegrasikan analisis semiotika dan evaluasi strategis untuk menjelaskan hubungan antara representasi media, relasi kekuasaan, dan perubahan sosial.